A participação da controladoria na responsabilidade social empresarial: um estudo nas empresas vencedoras do prêmio Delmiro Gouveia em responsabilidade social do ano de 2007 - Machado, Mônica Valesca Veras (2008)
As the theme of Corporate Social Responsibility (CSR) develops, companies have been pressed to play a new role, going being legal and financial demands. Within this perspective, Controllership, in fulfilling its support role to the decision-making process, must generate information that go beyond the accounting and financial sphere, encompassing even information in the Corporate Social Responsibility arena. At the beginning of the twenty-first century, modern management no longer allows accounting to be focused solely on financial issues; it demands accounting to operate in an environment that supports management and provides ethical, transparent and faithful information to all stakeholders. Aligned with this view, the purpose of this study is to investigate, in the context of companies that won the 2007 edition of Delmiro Gouveia´s award on Social Responsibility, the relevance of the controllership in the process of managing social responsibility. The research, carried out through a survey, can be classified as exploratory and descriptive. A questionnaire, based on the model used by the Ethos Institute of Social Responsibility, was uses to collect data. The work shows the present stage of the organizations in the face of practices of corporate social responsibility and the importance of the Controllership for the improvement of such practices. The results showed that the Controllership plays a critical role in the adoption, integration and gradual consolidation of the social responsibility practices, since the early stages of making the company aware of the theme until the control of the social responsibility practices.